Antibiotic Resistance and Ways to Overcome It. Commentary on the Article of Svetlana V. Ilyina «Irrational Use of Antibiotics in Medicine: Crisis of Antibiotic Resistance and what We Can Do» - Vladimir K. Tatochenko (Union of pediatricians of Russia, 2018)
.